ANTITHROMBOTIC THERAPY AT PERCUTANEOUS CORONARY INTERVENTIONS - V. A. Sulimov (Столичная издательская компания, 2016)
Possibilities of modern antiplatelet and antithrombotic therapy at percutaneous coronary interventions in patients with coronary artery disease are surveyed. Data of multicenter randomized clinical trials and meta-analyses are discussed. Possibilities of various drugs at percutaneous coronary interventions are reported from position of the international clinical guidelines.